ANALISIS PERBANDINGAN PAKAN RUMPUT DENGAN PAKAN PELEPAH DAN DAUN SAWIT PADA PETERNAKAN KAMBING DI KABUPATEN NAGAN RAYA - Dedy Darmansyah; Maulidil Fajri; Aseh Lestari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Goat farming in Indonesia is currently growing rapidly through the adoption of science and technology. However, this development is not evenly distributed throughout Indonesia, this is because some regions still apply livestock systems with limited existing knowledge. Based on the results of observations made, some goat breeders have started to use fronds and palm fronds from maintenance plants and do not have economic value in Nagan Raya District, Aceh Province. The use of palm fronds as ruminant feed ingredients requires beneficial treatment to reduce the lignin content found in palm fronds, one of the technologies used is fermentation, this is to improve feed quality. The purpose of this study was to determine the ratio of grass feed to fronds and palm leaf feed for goats in Nagan Raya District. This research was conducted in Nagan Regency by calculating the ratio of Total Cost, Total Revenue and Profit Analysis on farms using grass goat feed with fronds and palm leaf goat feed. Based on the results of this study, it was found that farmers who used fronds and palm leaves forage earned a greater profit of 69.97% compared to farmers who used regular grass feed. This significant difference was found in the cost of providing grass feed which is more expensive than oil palm feed. Meanwhile, based on the farmer's information, there is no difference between the two types of feed in terms of the cost of vitamins, drugs and care provided.